2000
DOI: 10.3758/bf03212116
|View full text |Cite
|
Sign up to set email alerts
|

Tones disappear faster in the right ear than in the left

Abstract: In order to gain further information on the characteristics and physiological correlates oftone decay in humans, the tone decay test was administered to 58 normal-hearing subjects, successively in the left and right ears and in absence and presence of a contralateral noise. The results revealed that tone decay was greater in the right than in the left ear and was increased by contralateral noise. The contralateral effect of this noise on cochlear biomechanisms was then estimated by measuring contralaterally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The site of stimulation is also shown to be a factor on the observed auditory cortex function. 28,29,31 However, effects of hand preference, ipsilateral, contralateral, and binaural stimulus presentation on the auditory cortex activation are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The site of stimulation is also shown to be a factor on the observed auditory cortex function. 28,29,31 However, effects of hand preference, ipsilateral, contralateral, and binaural stimulus presentation on the auditory cortex activation are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Functional differences between the cerebral hemispheres have been reported by previous studies. 26–31 Left hemispheric dominance has been implicated in the processing of verbal stimuli, whereas right hemispheric dominance for nonverbal stimuli is determined in right‐handed individuals. In the present study, all subjects were right handed, and left monaural stimulation was preferred to evoke activation because pure‐tone stimuli are processed predominantly in the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…At the peripheral level there is evidence that: (1) hearing sensitivity is better in the right ear (McFadden, 1993;McFadden and Mishra, 1993); (2) the prevalence of spontaneous otoacoustic emissions is greater in the right ear (McFadden, 1993;Khalfa and Collet, 1996); (3) transient otoacoustic emission amplitudes are greater in the right ear (Khalfa et al, 1998a,b), (4) tone decay is greater in the right ear (Khalfa et al, 2000); (5) temporary threshold shift is greater in the left ear (Khalfa and Collet, 1996); (6) tinnitus is more prevalent in the left ear (Khalfa et al, 1997); and (7) the medial olivo-cochlear efferent system is more effective on the right side (Khalfa et al, 1998a,b).…”
Section: Auditory Asymmetrymentioning
confidence: 96%
“…It has been suggested that OAE asymmetries are attributable to asymmetries in MOC effect (Morlet, Goforth, Hood, et al, 1999). Various data indicate that there are asymmetries in MOC effect and that these covary with gender and handedness (Khalfa, Veiullet, & Collet, 1998;Khalfa, Micheyl, Pham, et al, 2000), but it is not known whether these produce the OAE asymmetry. An interesting tie between cortical asymmetry and MOC effect asymmetry is suggested by the observations that there are more benzodiazepine receptors in the left than in the right cortex, and that benzodiazepine ingestion reduces contralaterally elicited MOC suppression in the right ear but has little such effect in the left ear (Morand, Bouvard, Ryvlin, et al, 2001;MorandVilleneuve, Veiullet, Perrot, et al, 2005).…”
mentioning
confidence: 97%